MicroRNA mimicry blocks pulmonary fibrosis. Issue 10 (19th September 2014) - Montgomery, Rusty L; Yu, Guoying; Latimer, Paul A; Stack, Christianna; Robinson, Kathryn; Dalby, Christina M; Kaminski, Naftali; van Rooij, Eva
Abstract Over the last decade, great enthusiasm has evolved for microRNA (miRNA) therapeutics. Part of the excitement stems from the fact that a miRNA often regulates numerous related mRNAs. As such, modulation of a single miRNA allows for parallel regulation of multiple genes involved in a particular disease. While many studies have shown therapeutic efficacy using miRNA inhibitors, efforts to restore or increase the function of a miRNA have been lagging behind. The miR‐29 family has gained a lot of attention for its clear function in tissue fibrosis. This fibroblast‐enriched miRNA family is downregulated in fibrotic diseases which induces a coordinate increase of many extracellular matrix genes. Here, we show that intravenous injection of synthetic RNA duplexes can increase miR‐29 levels in vivo for several days. Moreover, therapeutic delivery of these miR‐29 mimics during bleomycin‐induced pulmonary fibrosis restores endogenous miR‐29 function whereby decreasing collagen expression and blocking and reversing pulmonary fibrosis. Our data support the feasibility of using miRNA mimics to therapeutically increase miRNAs and indicate miR‐29 to be a potent therapeutic miRNA for treating pulmonary fibrosis.